2012
DOI: 10.1371/journal.pone.0033940
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Induced Erythroid Differentiation of K562 Cells Mimics the Central Macrophage Milieu in Erythroblastic Islands

Abstract: Growing evidence supports the role of erythroblastic islands (EI) as microenvironmental niches within bone marrow (BM), where cell-cell attachments are suggested as crucial for erythroid maturation. The inducible form of the enzyme heme oxygenase, HO-1, which conducts heme degradation, is absent in erythroblasts where hemoglobin (Hb) is synthesized. Yet, the central macrophage, which retains high HO-1 activity, might be suitable to take over degradation of extra, harmful, Hb heme. Of these enzymatic products, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…As CO has profound effects on mitochondrial and cellular respiration and other hemoproteins , it may have positive effects on erythroid differentiation. A previous study reported that HO‐1 and CO induced the erythroid differentiation of K562 cells under anoxic conditions. Garcia‐Santos et al .…”
Section: Discussionmentioning
confidence: 92%
“…As CO has profound effects on mitochondrial and cellular respiration and other hemoproteins , it may have positive effects on erythroid differentiation. A previous study reported that HO‐1 and CO induced the erythroid differentiation of K562 cells under anoxic conditions. Garcia‐Santos et al .…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, the lack of HO-1 expression in erythroblasts is well described in both K562 erythroid cell line (7) and primary human bone marrow-derived erythroid progenitors (7). Oppositely, HO-1 is constitutively expressed in macrophages; therefore, it has been suggested that HO-1 activity in these cells is crucial to regulate erythropoiesis (211). Indeed, exogenous CO accelerated the differentiation of K562 cells in vitro (211).…”
Section: Ho-1mentioning
confidence: 99%
“…Oppositely, HO-1 is constitutively expressed in macrophages; therefore, it has been suggested that HO-1 activity in these cells is crucial to regulate erythropoiesis (211). Indeed, exogenous CO accelerated the differentiation of K562 cells in vitro (211). Moreover, in the in vivo model of HO-1 + / -bone marrow transplantation, the differentiation of erythroblasts was impaired (30).…”
Section: Ho-1mentioning
confidence: 99%
“…9,10 However, the amount of Hb subsequently produced is greatly inferior to that produced by RBCs. 11 In contrast, immortalized human-induced pluripotent stem cellderived erythroid progenitor (HiDEP) cell lines can constitutively synthesize Hb, and these cells are deep red in color, even before differentiation. 12 Therefore, HiDEP cell lines are expected to be a novel source of cells for the generation of reagent RBCs for screening for unexpected antibodies because of their unique characteristics.…”
Section: Resultsmentioning
confidence: 99%